(untitled) (مجلة إحالات, 2026)
Generally, any academic researchers are confronted in their writing processes during the research path with some procedures that they should take into consideration while conducting their scientific papers and dissertations by checking their credibility. Especially in a time when everything is appearing as just a review or a forgery for what had been already saying, and to face the nightmare of plagiarism which is a serious, yet widespread type of research misconduct. Fortunately, the academic community is devoting great energy to help academicians by useful perspectives to avoid the pitfalls of plagiarism that can damage the scientific reputation and authentic contributions of researchers.